PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN LINGKUNGAN DESA HANUA PULANG PISAU KALIMANTAN TENGAH - Halim, Abdul; Rahayu, Helda; Anastasia S., Clara; Ika Susanti, Devita; Maharani N., Grace; Dio, Noperi; Priskila, Resty; Riko; Prima Sitepu, Rizal; Nurhani, Sarina; Bellamy D., Yorick; Yusnia; Dewi P.K., Wulan; Juanabel R., Zefanya (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Regular Thematic Community Service (KKN-T) Period I in 2024 was held in Hanua Village, Banama Tingang District, Pulang Pisau Regency, Central Kalimantan, with the main objective of improving community welfare through the application of science by students of Palangka Raya University. This KKN program carries the theme "UPR Contributes, Village Innovates" and includes various activities, including increasing literacy, preventing stunting, empowering MSMEs, and environmental management. The implementation of KKN in Hanua Village, which is a lowland area with an economy based on agriculture and mining, lasted for 43 effective days. The main activities carried out, such as the "Environmentally Caring Village" and "Yard Land Utilization" programs, succeeded in increasing public awareness of the importance of protecting the environment and utilizing resources optimally. In addition, supporting activities, such as "Literacy Village" and "Stunting-Free Village," contributed to improving the quality of education and public health. The results of the activities showed an increase in community participation in various programs, increased awareness of the importance of the environment, and strengthened social relations among residents. This program also succeeded in bringing positive changes to the Hanua Village community and providing valuable experience for students. Suggestions resulting from this activity include increasing women's participation in village government, sustainability of programs that have been implemented, further collaboration with related agencies, continuous evaluation and monitoring, and development of village facilities and infrastructure.